PATIENT PERCEPTIONS OF SERVICE QUALITY IN THE DENTAL POLYCLINIC OF SUNAN KALIJAGA REGIONAL GENERAL HOSPITAL DEMAK: A STUDY ON BPJS AND NON-BPJS PATIENTS - Erdianto Setya Wardhana; Nurul Laelatul Badriyah (Universitas Muhammadiyah Semarang, 2023)
Background: The Social Security Organizing Agency (BPJS) is an initiative by the government to improve the quality of healthcare services. However, in reality, the services provided to BPJS patients have not yet reached optimal standards. The objective of this research is to identify patients' perceptions regarding the quality of services between BPJS and non-BPJS patients in the dental clinic of Sunan Kalijaga Regional General Hospital (RSUD) in Demak.Method: This research was conducted at the Dental Clinic of Sunan Kalijaga Regional General Hospital (RSUD) in Demak in the year 2020, using an observational analytical approach based on a cross-sectional design. The sample was selected using the slovin technique, with a total of 78 respondents divided into two groups, namely 39 respondents who were BPJS participants and 39 other respondents who were not BPJS participants.Result: The research results showed differences in SERVQUAL service quality scores between patients who were participants of BPJS and those who were not BPJS participants. Based on the analysis of both groups across the dimensions, reliability had gap scores of -0.7 and -0.9, tangible evidence had gap scores of -0.5 and -0.6, responsiveness had gap scores of -0.9 and -1, assurance had gap scores of -0.4 and -0.4, and empathy had gap scores of -0.4 and -1.1. These scores obtained a significance value (p<0.05),Conclusion: There were significant differences in patient perceptions between the quality of patient services for BPJS participants and non-BPJS patients.